2020
DOI: 10.3389/fmars.2020.00727
|View full text |Cite
|
Sign up to set email alerts
|

Biofouling on Salmon Pen Nets and Cleaner Fish Shelters Does Not Harbor Planktonic Stages of Sea Lice

Abstract: The objective of the current study was to determine the extent to which planktonic sea lice (Lepeophtheirus salmonis Krøyer, 1838 and Caligus elongatus Nordmann, 1832) were present in the biofouling on open-sea net pens used for commercial rearing of Atlantic salmon (Salmo salar L.), and to assess if biofouling organisms on nets act as barriers similar to salmon lice skirts. We have examined two possible interactions of biofouling and planktonic sea lice, the first was if biofouling could function as a microha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Densities of planktonic sea lice can be described by mean abundance or a combination of the proportion-non-zero and average density (Jevne et al, 2020).…”
Section: Registration Of Planktonic Sea Licementioning
confidence: 99%
“…Densities of planktonic sea lice can be described by mean abundance or a combination of the proportion-non-zero and average density (Jevne et al, 2020).…”
Section: Registration Of Planktonic Sea Licementioning
confidence: 99%
“…Cleaning of marine nets releases biofouling debris that can contribute to thrombi/subacute vascular lesions in the gills, although such effects may be limited to a small proportion of fish over short periods (Ostevik et al 2021). Early studies suggested biofouling communities may support microbial communities that lead to amoebic gill disease outbreaks (Tan et al 2002), but a more recent study suggests that is not the case (Jevne et al 2020). It appears net cleaning may be an important management procedure that can impact welfare by improving water flow or removing harmful organisms.…”
Section: Pen Design and Maintenancementioning
confidence: 99%
“…Namely, the presence of biofouling in open-sea Atlantic salmon cages showed no influence on the average density and proportion of samples with planktonic stages of sea lice, nor the planktonic sea lice inhabited biofouling. 123 While the Atlantic salmon and gilthead seabream farming technologies, as well as ecological and biological traits of the two pathogens, do not allow for direct comparison and drawing of generalised conclusions, the former study could serve as a robust background for similar research in the Mediterranean.…”
Section: Host Responsementioning
confidence: 99%